Bureaucratic Culture, Ethical Leadership, and Communication in LLDIKTI Region VII, Indonesia - Rachma Tistasari (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2023)
This study investigates the impact of bureaucratic culture, ethical leadership, and communication climate on the performance of LLDIKTI Region VII civil servants, a key institution under the Indonesian Ministry of Education and Culture responsible for managing private universities in a specific region. A total of 80 civil servants participated as respondents. Data were collected using questionnaires and analyzed through Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that bureaucratic culture and ethical leadership significantly and positively influence the performance of LLDIKTI Region VII civil servants. Furthermore, communication climate moderates the relationships between both bureaucratic culture and ethical leadership, and civil servant performance. The results highlight the importance of fostering positive bureaucratic culture, promoting ethical leadership, and nurturing a healthy communication climate to enhance performance in private university management. These findings have implications not only for the Indonesian context but also for similar organizations globally, emphasizing the need to explore the generalizability of these results and investigate additional moderating factors that may influence organizational culture, leadership, and performance.